Investigation of Hungarian forest health condition with special respect to climate change (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The defoliation and crown dieback data of trees are typical indicators of forest health condition. In Hungary the data are collected in the frame of the national forest monitoring program and based on Forest Protection Network from 1987. In the paper these two data lines are investigated: (i) trend analysis was performed in respect of the examined time period according to different criteria, (ii) the relationships between healthy features and basic and derived climatic variables were examined by correlation analysis. The paper gives a general overview of the Hungarian forest health condition. Detectable general trends and statistically significant relationships are defined for all examined species and for 12 groups (subsets) of species. The received general results help us to determine further directions of deeper and more detailed investigations.